Development and characterization of an equine behaviour chamber and the effects of amitraz and detomidine on spontaneous locomotor activity - Harkins, J. D.; QueirozNeto, A.; Mundy, G. D.; West, D.; Tobin, T. (Blackwell Science, 1997)
This report describes the development of a behaviour chamber and the validation of the chamber to measure locomotor activity of a horse, Locomotor activity was detected by four Mini-beam sensors and recorded on a data logger every 5 min for 22 h. Horses were more active during daytime than in the evening, which was at least partially related to human activity in their surroundings. To validate the ability of the chambers to detect changes in activity, fentanyl citrate and xylazine HCl, agents well-characterized as a stimulant and a depressant, respectively, were administered to five horses. Fentanyl citrate (0.016 mg/kg) significantly increased locomotor activity which persisted for 30 min, Xylazine HCl (1 mg/kg) significantly reduced locomotor activity for 90 min. Amitraz produced a dose-dependent decrease in locomotor activity, lasting 75 min for the 0.05 mg/kg dose, 120 min for the 0.10 mg/kg dose, and 180 min for the 0.15 mg/kg dose, In a separate experiment, yohimbine administration immediately reversed the sedative effect of amitraz, This suggests there is a similarity in the mode of action of amitraz, xylazine and detomidine, as yohimbine acts primarily by blocking central alpha 2-adrenoceptors that are stimulated by agents like xylazine, There was also a significant decrease in locomotor activity following injection of detomidine (0.02, 0.04 and 0.08 mg/kg) for 1.5, 3.5 and 5.0 h, respectively, the locomotor chamber is a useful, sensitive and highly reproducible tool for measuring spontaneous locomotor activity in the horse, which allows investigators to determine an agent's average time of onset, duration and intensity of effect on movement.